Aeolian sediment transport pathways and aerodynamics at troughs on Mars - BOURKE, MARY (My University, 2004)
Interaction between wind regimes and topography can give rise to complex suites of aeolian landforms. This paper considers aeolian sediment associated with troughs on Mars and identifies a wider range of deposit types than has previously been documented. These include wind streaks, falling dunes, ``lateral?? dunes, barchan dunes, linear dunes, transverse ridges, sand ramps, climbing dunes, sand streamers, and sand patches. The sediment incorporated into these deposits is supplied by wind streaks and ambient Planitia sources as well as originating within the trough itself, notably from the trough walls and floor. There is also transmission of sediment between dunes. The flow dynamics which account for the distribution of aeolian sediment have been modeled using two-dimensional computational fluid dynamics. The model predicts flow separation on the upwind side of the trough followed by reattachment and acceleration at the downwind margin. The inferred patterns of sediment transport compare well with the distribution of aeolian forms. Model data indicate an increase of wind velocity by 30% at the downwind trough margin. This suggests that the threshold wind speed necessary for sand mobilization on Mars will be more frequently met in these inclined
PUBLISHED
Keywords: Mars; Smart & Sustainable Planet